Is fluoroscopy-guided percutaneous rupture of facet cyst an alternative to surgery? A case report - GÜNDÜZ, OSMAN HAKAN; ŞENCAN, SAVAŞ (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2018)
Lumbar intraspinal synovial cysts (LISCs) are rare cause of the lumbosacral radicular syndrome. Fluoroscopy-guided percutaneous cyst rupture (PCR) is an option in the treatment. This report introduces long-term symptom relief after fluoroscopy-guided PCR of LISC. A 73-year-old patient presented with low back pain radiating to right leg. L5 radiculopathy was suspected by physical examination; however, an intraspinal cystic mass was visualized through imaging studies. The patient reported immediate pain relief after fluoroscopy-guided PCR, which sustained for one year. In conclusion, fluoroscopy-guided PCR appears to be a safe and effective treatment option and should be considered before surgery in patients with LISCs.
Keywords: Fluoroscopy-guided percutaneous cyst rupture; low back pain; lumbar intraspinal synovial cyst; LUMBAR SYNOVIAL CYSTS; SURGICAL-MANAGEMENT; DIAGNOSIS